The history of the jewelry art of the people of Surkhandarya and the Khorezm oasis of the Bronze Age: types, typology, commonalities and differences (Multidisciplinary Journal of Science and Technology, 2024)
This article is devoted to the study of the history, types, typology of Bronze Age jewelry in Surkhandarya and Kharezm oases, as well as their commonalities and differences. The results of the research will help to better understand the cultural and social aspects of these regions.